Factors of Carbon Emission Disclosure by Moderation of Company Size in Mining Sector Companies - Fitriani, Lusiana; Sunarsih, Uun (Green Publisher Indonesia, 2024)
This research aims to determine the role of environmental performance, profitability and emission volume in increasing the spread of carbon emissions by moderating company size. This research uses quantitative methods with causality and the data methods used in this research are descriptive statistics, panel data regression, classical assumption tests, hypothesis tests and coefficient of determination using Eviews 12. The population of this research is mining sector companies listed on the Stock Exchange Indonesia from 2019 to 2022. The sample was determined based on the purposive sampling method, with a sample size of 20 so that the total observations in this study were 78 observations. The data used in this research is secondary data. The data collection method uses the documentation method via the official website www.bei.co.id Hypothesis testing uses the t test. Based on the results of panel data linear regression, it shows that the influence of environmental performance with carbon emission disclosure explains that environmental performance is the company's ability to create a green and clean environment. In accordance with legitimacy theory, social relations between companies and society require companies to comply with norms that apply in society, one of which is by protecting the environment, if the company wants to gain legitimacy from society. Then company size can moderate the influence of environmental performance and emission volume on carbon disclosure. The reason company size moderates environmental performance on the disclosure of carbon emissions is that the higher the level of assets of a company, the greater or greater the disclosure of social information made by the company. So it provides a commitment to the interests of the company but must provide benefits to its stakeholders. So that partial profitability has no effect on carbon emissions disclosure, while the volume of carbon emissions has an effect on carbon disclosure.